Meta cognição: articulações teóricas, possibilidades didáticas e de formação docente - Boszko, Camila (2023)
Metacognition concerns the control of cognitive processes by the subject himself in view of the ability to become aware of his knowledge and control his actions. The term, coined by the American psychologist John Hurley Flavell in the 1970s, was initially linked to memory studies and later became part of the field of cognition. Its understanding has undergone adaptations and adaptations to the different areas of knowledge that use it, causing a diversity of definitions, models and associated elements. Despite this diversity of understandings, studies indicate that the use of metacognition as a learning strategy has had an impact on the qualification of this process. However, these same studies highlight gaps in terms of the theoretical body, such as: lack of a consensual understanding or model, or even a metacognitive theory; difficulty in identifying instruments that can assess the use of metacognitive thinking in learning situations; and, the absence of studies in initial or continuing teacher training courses. Based on the above, through a qualitative, interpretationist and descriptive study, the present study aimed to identify the foundations and conceptual bases of metacognition, evaluating its presence in didactic actions and continuing education courses for teachers guided by reflection and examining the foundations of metacognition and how it can be present in the educational context. More specifically, it sought answers to four questions, namely: 1. What theoretical contributions support the understanding of metacognition based on what is brought by Flavell? 2. What models can we identify from this understanding of metacognition? 3. In the field of didactic intervention in Biology, what are the instruments used in research that seeks to associate the activation of metacognitive thinking as an element of the teaching-learning process? 4. What metacognitive characteristics are observed in the design of a continuing education course for university teachers focused on the action-reflection perspective? In the first case, it was possible to identify the bases of metacognition in the studies of John Dewey and Jean Piaget, which reinforces its understanding as a reflective process focused on awareness. In the second question, the existence of nine metacognitive models was identified, each with distinct elements associated with its object or field of study. In the third case, the results showed that questionnaires are researchers' preferred instruments. However, others, such as learning diaries and records, have also been used as a way of identifying the presence of metacognition in the structure of students' thinking during learning activities. Finally, regarding the fourth question, it was possible to identify metacognitive characteristics in the design of a continuing teacher training course, structured from the theoretical and practical perspective of action-reflection, which shows the approximation between metacognitive thinking and reflective thinking in the form as discussed in the course. This approach raises the possibility that metacognitive strategies can be introduced explicitly in the actions designed for the course, reinforcing their contribution to the qualification of the continuing education process of teachers participating in the course